Écrire vers là où on ne sait pas : le secret pour horizon - Julien Daillère (Symbolon, 2020)
To Write Towards Where We Don't Know: Secret as a Horizon Writing can be considered as a way to unveil unconscious secrets, as Beckett and Bauchau seem to have tried in their works. This led them to an intimate confession, more or less transparent for themselves and the others. How did they deal with that? Angelica Liddell claims that she makes the "pornography of the soul", promising a true con¬fession. But her secret is fake: her intimate drama lays hidden behind the stage of “Todo el cielo sobre la terra” (“El síndrome de Wendy”). Spectators are trapped in hyperreality. Marie Payen's performance could look like one more exhibitionist show as it's about her father that she's never known. But “Je Brûle” is a confession which cannot be completed: it is perma¬nently reinvented with an improvised text. It reminds us of what we don't and will never know. Her only confession: there are secrets impossible to unveil.